Bronquiectasias não fibrocísticas: um perfil epidemiológico em hospital pediátrico - Brenda Souza de Oliveira Reis; Ângelo Antônio Gonçalves de Quadros; Raisa Elena Tavares Pinheiro (Sociedade Brasileira de Pediatria, 2024)
OBJECTIVES: to describe the epidemiological profile of patients with non-cystic fibrosis bronchiectasis in a pediatric hospital and to expand the knowledge of this comorbidity in the pediatric population. METODOLOGY: Chest CT scans performed from January 2016 to January 2020 in a pediatric care service were selected. The reports were consulted, verifying those with compatible criteria currently accepted for the diagnosis of bronchiectasis. The medical records of those selected underwent a review process in search of the variables analyzed. Patients diagnosed with cystic fibrosis and with outdated medical records were excluded. RESULTS: Of the 2319 reports studied, 42 patients were identified. Among these, 59.5% were female, 66.7% were followed up at a pneumopediatrics outpatient clinic, and the mean age at the time of imaging diagnosis was 9.3 years (±4.9). At follow-up, 57.1% of patients underwent spirometry and 35.7% underwent sputum culture. The most observed bacterial growth was that of Pseudomonas aeruginosa (33.4%) and the most frequent spirometric pattern was restrictive (29.2%). Of the presumptive etiologies, the most prevalent was recurrent pneumonia (21.4%), followed by bronchiolitis obliterans (14.3%) and collagen diseases (14.3%). CONCLUSION: The results found in this study allowed a better characterization of this subgroup of patients. In addition, the importance of diagnosing non-cystic fibrosis bronchiectasis is reinforced, as its therapy requires specific and individualized management.